Ambedkar - "Omvedt, Gail" (New Delhi, 2004)
Born in 1891 into an untouchable family, Dr Bhimrao Ramji Ambedkar is the acknowledged modern Indian leader of the struggle against social injustice. In this concise biography, eminent scholar Gail Omvedt presents the inspiring story of how Ambedkar got educated, overcame the stigma of untouchability and gradually rose to become a lawyer of international repute, a founder of a new order of Buddhism and a framer of India$1 (Bs Constitution. She contextualizes Ambedkar$1 (Bs argument with the elite nationalists, particularly Gandhi, that India could never be truly free without the liberation of its most oppressed sections.s
Keywords: B.R.Ambedkar- Biography